Freedom, repression, and private property in Russia - Shlapentokh, Vladimir; Arutunyan, Anna (Cambridge University Press, 2013)
Demonstrates how the emergence of private property and a market economy after the Soviet Union's collapse enabled a degree of freedom while simultaneously supporting authoritarianism.